2019
DOI: 10.1002/jcp.28078
|View full text |Cite
|
Sign up to set email alerts
|

Efficient osteogenic differentiation of the dental pulp stem cells on β‐glycerophosphate loaded polycaprolactone/polyethylene oxide blend nanofibers

Abstract: Hard tissue lesion treatment in oral and maxillofacial has been challenging because of tissue complexities. This study aimed to investigate novel biopolymeric construct effects on the osteogenic differentiation potential of the dental pulp stem cells (DPSCs) for introducing a cell copolymer bioimplant. A blended polycaprolactone (PCL)‐polyethylene oxide (PEO) was fabricated using electrospinning, simultaneously filled by β‐glycerophosphate (β‐GP). After that biocompatibility and release kinetics of the PCL‐PEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…The profile of gene expression of the DPSCs, which were seeded on the membranes control group in the osteogenic media, was consistent with the results of other studies 73,74 . Our findings showed that the new membranes enhanced the osteogenic properties of the collagenic membranes.…”
Section: Resultssupporting
confidence: 90%
“…The profile of gene expression of the DPSCs, which were seeded on the membranes control group in the osteogenic media, was consistent with the results of other studies 73,74 . Our findings showed that the new membranes enhanced the osteogenic properties of the collagenic membranes.…”
Section: Resultssupporting
confidence: 90%
“…The development of multipurpose composite polymer scaffolds, such as polyhydroxybutyrate (PHB)/chitosan/bioglass nanofibers [93] and β-glycerophosphate (β-GP)-loaded PCL/polyethylene oxide (PEO) blend nanofibers [94], promotes a paradigm shift of scaffolds from biocompatible cell transporters or simple delivery vehicles to biofunctional and guiding matrices. Further work should focus on assessing the synergetic effects between different polymer compositions and the added active therapeutics and cells.…”
Section: Synthetic Polymer Materialsmentioning
confidence: 99%
“…However, they can be more easily and non-invasively gained from removed teeth in comparison with BMSCs. Accumulating evidence has proved the potential of DPSCs in generating bone-like tissues and repairing bone loss [6][7][8]. For all these reasons, hDPSCs represent rising candidates for therapies of bone tissue repair.…”
Section: Introductionmentioning
confidence: 99%